2011
DOI: 10.1111/j.1745-4565.2011.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plant Essential Oils for Control of Postharvest Brown and Gray Mold Rots on Apricot

Abstract: In this study, antifungal activities of Thymus vulgaris L., Eugenia caryophyllata L., Cinnamomum zeylanicum Blume and Carum copticum L. essential oils against Monilinia fructicola and Botrytis cinerea, two important postharvest pathogens of stone fruit, were investigated under in vivo studies. Results showed that the essential oil treatments, especially T. vulgaris and E. caryophyllata oils, had a good antifungal activity in reduction of both disease incidence and disease severity of brown and gray mold rots c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 31 publications
6
26
0
2
Order By: Relevance
“…In agreement with the results obtained in this study, other studies have reported that the application of CS and EOs alone or in combination as a coating material preserved or improved the physical and physicochemical quality of fruits (Hassani et al 2012;Perdones et al 2012). For example, Xing et al (2011) showed that the use of coatings composed of CS (10, 000 ppm) and CEO (2500 ppm) was effective in reducing the microbial deterioration of sweet peppers throughout 35 days of storage at room temperature.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the results obtained in this study, other studies have reported that the application of CS and EOs alone or in combination as a coating material preserved or improved the physical and physicochemical quality of fruits (Hassani et al 2012;Perdones et al 2012). For example, Xing et al (2011) showed that the use of coatings composed of CS (10, 000 ppm) and CEO (2500 ppm) was effective in reducing the microbial deterioration of sweet peppers throughout 35 days of storage at room temperature.…”
Section: Discussionsupporting
confidence: 92%
“…According to the reports, the inhibitory mechanism of trans ‐cinnamaldehyde may be that the CHO group was hydrophilic, which could easily absorb the hydrophilic group on the surface of bacteria or fungi and penetrate into the cell wall. The destruction of the outer membrane enhanced cell membrane permeability, causing material run off and resulting in cell death . At present, many experiments have indicated that trans ‐cinnamaldehyde has good antifungal effect.…”
Section: Resultsmentioning
confidence: 99%
“…exert different biological actions on the physiological behaviour of postharvest pathogens . To establish the fungicidal properties of essential oils, several investigations have been conducted over the past few years, and there are a number of reports evincing the application of essential oils for the control of storage moulds …”
Section: Introductionmentioning
confidence: 99%